Working Alliance as a Mediator between Supervisory Styles and Supervisee Satisfaction - Dan Li; David K. Duys; Yanhong Liu (Teaching and Supervision in Counseling, 2021)
To answer the research question whether there is a mediation effect of the supervisory working alliance between supervisory styles and supervisee satisfaction, we developed a mediation model and tested this hypothesized mediation effect with a sample of 111 participants that was comprised of master’s and doctoral counselor trainees and counseling practitioners recruited from several counseling professional networks. Results indicated a statistically significant indirect effect of supervisory styles on supervisee satisfaction through the supervisory working alliance. Specifically, when supervisees rated higher on a mixture of three supervisory styles, they were more likely to report a stronger working alliance with their supervisors; this alliance, in turn, contributed to their higher levels of satisfaction with supervision. These findings also speak to the importance of maintaining a flexible, balanced approach in supervision, and shed light on how both supervisors and supervisees can contribute to the supervisory working alliance so as to enhance supervisee satisfaction.
Keywords: supervisory styles; supervisory working alliance; supervisee satisfaction; mediation analysis